Genetic variants in the PSMA6, PSMC6 and PSMA3 genes associated with childhood asthma in Latvian and Taiwanese populations - Paramonova, N.; Wu, L.ShiShin; Rumba-Rozenfelde, I.; Wang, J.Y.; Sjakste, N.; Sjakste, T. (Вiopolymers and Cell, 2014)
Proteasomes mediate functional realization of signaling proteins implicated in asthma pathogenesis. Aim. To evaluate main and sex-specific association between the PSMA6, PSMC6 and PSMA3 proteasomal genes variations and childhood asthma in Latvians and Taiwanese. Methods. SNPs rs2277460, rs1048990, rs2295826, rs2295827 and rs2348071 were genotyped in 102 Latvian and 159 Taiwanese cases for comparison with genetic diversity in populations (191 and 1097 subjects respectively). Results. Haplotype CGACG showed strong (P < 0.0001) association with asthma risk in both populations. All loci heterozygous genotypes and haplotype CCGTA were identified as asthma risk factors in Latvians; rs1048990 and rs2348071 GG homozygotes and rs2295826 and rs2295827 heterozygotes showed asthma risk and protective effect in Taiwanese females respectively. The multi locus genotypes homozygous for alleles being common in Latvian population were identified as protective in Latvians and disease susceptible in Taiwanese. Conclusions. Our results suggest an association of the 14q13-23 proteasomal genes polymorphisms with the childhood asthma in Latvians and Taiwanese and high-light risk and/or protective factors being the same or different between the populations.